2006
DOI: 10.1007/s00125-006-0539-2
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth factor-1 and epithelial haemato–retinal barrier breakdown: potential implication in the pathogenesis of diabetic retinopathy

Abstract: Aims/hypothesis Disruption of the retinal pigment epithelial (RPE) barrier contributes to sub-retinal fluid and retinal oedema as observed in diabetic retinopathy. High placental growth factor (PLGF) vitreous levels have been found in diabetic patients. This work aimed to elucidate the influence of PLGF-1 on a human RPE cell line (ARPE-19) barrier in vitro and on normal rat eyes in vivo. Methods ARPE-19 permeability was measured using transepithelial resistance and inulin flux under stimulation of PLGF-1, vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 33 publications
7
96
1
6
Order By: Relevance
“…The ARPE-19 cell line expresses several RPE-specific markers (CRALBP and RPE65) and forms polarized monolayers; however, the TER generated by these cells is normal at 40-70% less than the primary RPE cells in culture (Dunn et al 1996;Geisen et al 2006;Hartnett et al 2003;Jin et al 2002). In the current study, both primary cells and the ARPE-19 cell line produced monolayers that formed continuous tight-junctioned complexes between cells and generated TER that was consistent with previous studies (Dunn et al 1996;Geisen et al 2006;Miyamoto et al 2007). Although the TER values obtained in ARPE-19 cells were lower than those in primary porcine cells, the administration of VEGF to either cell type resulted in a robust (30-50%) drop in the TER within 5 hours of treatment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The ARPE-19 cell line expresses several RPE-specific markers (CRALBP and RPE65) and forms polarized monolayers; however, the TER generated by these cells is normal at 40-70% less than the primary RPE cells in culture (Dunn et al 1996;Geisen et al 2006;Hartnett et al 2003;Jin et al 2002). In the current study, both primary cells and the ARPE-19 cell line produced monolayers that formed continuous tight-junctioned complexes between cells and generated TER that was consistent with previous studies (Dunn et al 1996;Geisen et al 2006;Miyamoto et al 2007). Although the TER values obtained in ARPE-19 cells were lower than those in primary porcine cells, the administration of VEGF to either cell type resulted in a robust (30-50%) drop in the TER within 5 hours of treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In the vascular endothelium, VEGF increases paracellular permeability by the activation of VEGF-R2 receptors (Autiero et al 2003;Gille et al 2001;Shen et al 1999). However, a recent study by Miyamoto and colleagues concluded that the VEGF-R1 receptor subtype mediated VEGF-induced changes in the barrier properties of ARPE-19 cell monolayers (Miyamoto et al 2007). Like Miyamoto and colleagues, we identified VEGF-A 165 as an effective cytokine in regulating RPE barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, treatment of RPE cells with either serum, interferon-γ, tumour necrosis factor-α, hepatocyte growth factor (HGF), IL-1β or placental growth factor-1 (PLGF-1) increases permeability and alters the levels or content of tight junction molecules [14][15][16][17][18]. As IL-1β plays an essential role in the development of DR [19][20][21][22], we decided to use this cytokine to provoke the breakdown of the RPE cell monolayer and to test the potential preventive effects of fenofibrate.…”
Section: Introductionmentioning
confidence: 99%